The Influence of Knowledge Creation and Knowledge Sharing on Product Development with Product Innovation Mediation Empirical Study on The R&D Food Industry - Fedora Sanchia Tiyana; Budi Susanto; P.M. Winarno (Ridwan Institute, 2022)
In this study, the effect of knowledge creation and knowledge sharing on product development through the mediation of product innovation was investigated. This research was conducted because of the research gap in previous studies regarding the effect of knowledge creation and knowledge sharing on product development. This research is quantitative and was conducted by distributing questionnaires to food and beverage companies in Jakarta and obtaining 50 respondents. The data obtained were processed using SMART-PLS. According to the findings of this study, knowledge sharing has no significant effect on product development; knowledge creation has no significant effect on product development; knowledge creation has a significant positive effect on product innovation; knowledge sharing has a significant positive effect on product innovation; product innovation has a significant positive effect on product development; product innovation mediates the relationship between knowledge creation and product development, and product innovation mediates the relationship between knowledge sharing and product development. From the result, it can be suggested that the company needs to design activities, create internal company forums, create a database for the R&D department, and require employees to carry out activities outside the company. Both suggestions can be adapted to the majority of the working executives' generation. It is expected to be more effective in implementation.